Bringing Radio into America's Homes: Marketing New Technology in the Great Depression. Issue 2 (1st June 2016) - Scott, Peter; Walker, James T.
Abstract : We examine the early marketing and distribution of entertainment radio sets. Manufacturers used distribution networks to both maximize profits and create barriers to entry. Lacking the market power of auto manufacturers, they developed cooperative strategies with authorized distributors and dealers. Dealers often complained about the costly activities manufacturers required of them. However, these underpinned the dominant quality and branding competition model of the 1920s, while the Depression-era switch to a simpler radio format, sold on price, proved catastrophic for the specialist retailer.